Effect of jujube pulp on the quality of cream cheese product during storage - Bingshou Wang; Xiuli Ma; Fang Wang; Guoying Qi; Mingyue Chen; Anna Liu; Wanning Fan (Journal of Dairy Science)
ABSTRACT: Cheese is favored by foreign consumers for its remarkable nutritional profile and unique taste. However, Chinese consumers find it difficult to accept its strong flavor profile. Therefore, it is imperative to develop a cheese product that meets the flavor preferences of Chinese consumers. In this study, jujube pulp was used to partially substitute cow milk (0%, 5%, 10%, 15%, 20%; wt/wt) to develop cream cheese products. The effect of different amounts of jujube pulp on the composition, texture, rheology, microstructure, and sensory properties of cream cheese products during storage was investigated. The results showed that at the same storage time, the moisture content and yield of the product increased as the amount of jujube pulp increased, and both protein content and fat content decreased. In addition, hardness, and storage modulus decreased, protein cross-linking was disrupted, serum channels were enlarged, and jujube flavor and smoothness scores increased, whereas cream flavor scores decreased. At the same amount of jujube pulp, the soluble nitrogen content of the product increased during storage, while the hardness and storage modulus decreased, and the sensory score peaked at 7 d. Principal component analysis revealed positive relationships between protein content, fat content, hardness, and storage modulus of the product, whereas these parameters showed negative relationships with moisture content and jujube flavor. The cream cheese products with 10% and 15% jujube pulp showed the best sensory quality. This study will provide a theoretical basis for the quality control of jujube flavored cream cheese products and technical support for the development of cheese products tailored to the preferences of Chinese consumers.